Developing Materials of English Phonetics and Phonology for ELT Departments At Islamic Higher Education Institutions Based on Integration Paradigm - Toyyibah Toyyibah (Didaktika Religia, 2021)
Islamic higher education institutions (PTKIs) are mandated to implement science integration. As a non-religious program, ELT Department in PTKIs should respond to this mandate by implementing the science integration in the curriculum. The present article reports the results of a Research and Development study that developed the materials of English Phonetics and Phonology for ELT Departments at PTKIs. Adapting the System Approach of Dick and Carey (2001), the study has developed through the steps of Need Analysis, Developing Preliminary Form of Product, Expert Validation, Revision 1, Field testing, Revision 2, and Final product. The integration of Islamic values with the materials started from designing the course objective which was then elaborated in the learning outcome and the topic. The learning outcomes or the course objectives were also developed by referring to the points of Indonesian national qualification framework for the graduates of undergraduate education level.